Dona Dominga: beyond the stairs of power - Nunes, Fabíola Fraga; Moreira, Fabricio do Rosário; Miranda , Giuliano; Cirillo , José (Farol, 2024)
The research aims to enter the human aspect of public monuments in the city of Vitória, and possibly verify the existence of a mortal aura, existing not apparently invisible. You will investigate Dona Dominga, the statue and at the same time, Dominga, the woman. Known by her contemporaries, however, almost invisible over the time she "lies" on the stairs of the capixaba government palace, resistant as a bronze, alive as a woman. In this context, the "dialogue" with the author of the work, the Italian based in Vitória, Carlo Crepaz, will be essential.